Multilevel Cryptography with Metadata and Lock Approach for Storing Data in Cloud - Annappaian, Dinesha Hagare; Agrawal, Vinod Kumar (Discoveries in Agriculture and Food Sciences, 2015)
Cryptography is a technique for secure communication. Cryptography main objectives are confidentiality, integrity, non-repudiation, availability and authentication. Cryptography is a well defined and used technique to secure sensitive data. It has been using in cloud computing technology by various cloud service provider. Customers across the world are looking for storage infrastructure to store huge amount of data securely. Hence they are opting on demand, ready available, internet based and maintenance free infrastructure known as cloud data storage as a service. Many potential vendors like Microsoft and Amazon providing this service to customer across the globe. But major challenge is customer trust on vendor. Vendor has to prove customer that their data is safe via cryptography, security breach penalty, policies and security agreement so on. However, it is difficult to gain customer confident on vendor security. Hence we are proposing customer end algorithm called multilevel cryptography for secure cloud data storage where customer performs multiple cryptography operations on their data before storing into a cloud. In this paper we present the multilevel cryptography algorithm for secure cloud data storage with design and analysis.